2015
DOI: 10.1155/2015/387896
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of HIV in Cancer Patients at the Surgical Oncology Unit of Donka University Hospital of Conakry (Guinea)

Abstract: Aim. To determine the prevalence of HIV infection among patients seen at the surgical oncology unit of Donka (Conakry, Guinea). Method. We conducted a retrospective and descriptive study of HIV infection in cancer patients from May 2007 to December 2012. Social characteristics (age, gender, marital status, and education) and immune status (HIV type, CD4 count) were reviewed. Results. Out of 2598 cancer patients, 54 (2.1%) tested positive for HIV. There were 11 (20.4%) defining AIDS and 43 (79.6%) nondefining A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…Among these, the most common was NHL, followed by cervical cancers. These ndings were similar to that reported by Venkatesh et al and Traore et al (11,25) . There were no reported cases of Kaposi's sarcoma in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among these, the most common was NHL, followed by cervical cancers. These ndings were similar to that reported by Venkatesh et al and Traore et al (11,25) . There were no reported cases of Kaposi's sarcoma in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…However, the bene t of ART therapy did not reduced risk of development of Hodgkin's lymphoma and other non-AIDS de ning malignancies. 16 In the present series, majority of the patients (72%) had a non-AIDS de ning malignancies similar to the nding by Traore et al 25 . The cases in the present study included malignancies of the oral cavity, nasopharynx, larynx, female genital tract, haematolymphoid malignancies, lung, GIT including anal canal, breast carcinoma, male genital tract, eye, urinary tract and metastatic lesion with an unknown primary.…”
Section: Discussionsupporting
confidence: 87%
“…This prevalence is in line with the study in KwaZulu-Natal, South Africa with the prevalence of 21% [ 9 ]. On the other hand, the result of this study is higher than the studies conducted in Ethiopia 13.3% [ 10 ], South Africa 7.2% [ 11 ], Nigeria 6%[ 12 ], Kenya 1.5% [ 13 ] and Guinea 2.1% [ 14 ]. This might be due to variations in the sample size, study period, study area and population.…”
Section: Discussioncontrasting
confidence: 78%
“…6 were reported HIV positive and out of this 6 cases reported only 5 had HIV+ Cancer .In our based study, we observed low proportion of HIV (0.28%) as well as HIV+ Cancer(0.23%) in cancer patients. Studies in this regards showed a high Proportion (2.1%) of the HIV infection in patients with cancer in surgical oncology unit ( 10,11 ). In a report from Maharashtra proportion of HIV was 1.2% (11 ).…”
Section: Discussionmentioning
confidence: 98%